Insights from the yield, protein production, and detailed alkaloid composition of white (Lupinus albus), narrow-leafed (Lupinus angustifolius), and yellow (Lupinus luteus) lupin cultivars in the Mediterranean region - Valente, Inês M.; Sousa, Carla; Almeida, Mariana; Miranda, Carla; Pinheiro, Victor; Garcia-Santos, Sofia; Ferreira, Luís M. M.; Guedes, Cristina M.; Maia, Margarida R. G.; Cabrita, Ana R. J.; Fonseca, António J. M.; Trindade, Henrique (Frontiers in Plant Science, 2023)
Lupins and other legumes have been considered alternative plant-based protein sources to soybeans for both humans and livestock and can contribute to more sustainable agricultural systems. The productivity and chemical composition of legumes is highly variable between species, cultivars and with the edaphoclimatic conditions. This work evaluated the adaptability of seven Lupinus cultivars of two different sowing locations, during two consecutive years, through the characterization of lupins seeds providing a tool to use them in a rational way. L. angustifolius cv. Tango and L. luteus cv. Acos were the most stable genotype across environments considering the seeds and protein production, while L. luteus cv. Alburquerque and L. luteus cv. Mister showed less variation in the total alkaloids content across environments. The edaphoclimatic conditions affected seeds and protein yields, as higher rainfall resulted in high productivity. The lower temperatures observed in the first year at both locations caused a reduced production of alkaloids in L. luteus cv. Acos and Cardiga. Due to the high alkaloid content of some of the studied cultivars their use as food or feed can pose some safety concerns. Still, these cultivars can have high resistance to herbivores and insects’ attacks which can be of utmost importance for the use of these crops for recovering poor or exhausted soils.